Residents' attitudes toward tourism development in Cua Lo - Le, Huy (H. : ĐHQGHN, 2020)
Findings from the study indicate that residents' perceptions about the impacts of tourism are related to the level of economic dependency on tourism. As the economy grows, the attitude of local residents becomes more positive. The development of new tourist spot contributing to the growth of local residents' income which lead Nghi Hai residents' attitudes become more positive in the coming years.